Epidemiology of Pemphigus in Turkey: One-year Prospective Study of 220 Cases - (:unkn) unknown (CROATION DERMATOVENEROLOGICAL SOC, 2017)
Pemphigus is a group of rare and life-threatening autoimmune blistering diseases of the skin and mucous membranes. Although they occur worldwide, their incidence shows wide geographical variation, and prospective data on the epidemiology of pemphigus are very limited. Objective of this work is to evaluate the incidence and epidemiological and clinical features of patients with pemphigus in Turkey. All patients newly diagnosed with pemphigus between June 2013 and June 2014 were prospectively enrolled in 33 dermatology departments in 20 different provinces from all seven regions of Turkey. Disease parameters including demography and clinical findings were recorded. A total of 220 patients were diagnosed with pemphigus during the 1-year period, with an annual incidence of 4.7 per million people in Turkey. Patients were predominantly women, with a male to female ratio of 1:1.41. The mean age at onset was 48.9 years. Pemphigus vulgaris (PV) was the commonest clinical subtype (n= 192; 87.3%), followed by pemphigus foliaceus (n= 21; 9.6%). The most common clinical subtype of PV was the mucocutaneous type (n= 83; 43.2%). The mean Pemphigus Disease Area Index was 28.14 +/- 22.21 (mean +/- Standard Deviation). The incidence rate of pemphigus in Turkey is similar to the countries of South-East Europe, higher than those reported for the Central and Northern European countries and lower than the countries around the Mediterranean Sea and Iran. Pemphigus is more frequent in middle-aged people and is more common in women. The most frequent subtype was PV, with a 9-fold higher incidence than pemphigus foliaceus.
Keywords: pemphigus; epidemiology; AUTOIMMUNE BULLOUS DISEASES; SEQUENCE-ANALYSIS; VULGARIS; REGION; SPECTRUM; TUNISIA; BETA